Cancer risk after cessation of asbestos exposure: a cohort study of Italian asbestos cement workers. Issue 3 (17th August 2007) - Magnani, C; Ferrante, D; Barone-Adesi, F; Bertolotti, M; Todesco, A; Mirabelli, D; Terracini, B
Abstract : Objectives: We aimed to study mortality for asbestos related diseases and the incidence of mesothelioma in a cohort of Italian asbestos cement workers after cessation of asbestos exposure. Methods: The Eternit factory operated from 1907 to 1986. The cohort included 3434 subjects active in 1950 or hired in 1950–86, ascertained from company records, without selections. Local reference rates were used for both mortality and mesothelioma incidence. Results: Mortality was increased in both sexes for all causes (overall 1809 observed (obs) vs 1312.3 expected (exp); p<0.01), pleural (135 obs vs 3.6 exp; p<0.01) and peritoneal (52 vs 1.9; p<0.01) malignancies and lung cancer (249 vs 103.1; p<0.01). In women, ovarian (9 vs 4.0; p<0.05) and uterine (15 vs 5.8; p<0.01) malignancies were also in excess. No statistically significant increase was found for laryngeal cancer (16 obs vs 12.2 exp). In Poisson regression analyses, the RR of death from pleural neoplasm linearly increased with duration of exposure, while it showed a curvilinear increase with latency and time since cessation of exposure. RR for peritoneal neoplasm continued to increase by latency, duration and time since cessation of exposure. RR for lung cancer showed a reduction after 15 years since cessation of exposure and levelled off after 40 years of latency. Conclusion: This study of a cohort of asbestos exposed workers with very long follow-up confirmed the reduction in risk of death from lung cancer after the end of exposure. It also suggested a reduction in risk for pleural mesothelioma with over 40 years of latency, while risk for peritoneal mesothelioma showed a continuing increase.